Electronic, transport, and magnetic properties of (Ca, Ba)(0.9)La0.1Fe1.9Pt0.1As2 compounds - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2019)
Superconductivity and magnetic properties were studied for La and Pt substituted (Ca, Ba)(0.9)La0.1Fe1.9Pt0.1As2 samples using structural, resistivity and magnetic measurement techniques. All bulk samples were synthesized by solid-state reaction method and annealed under a specific annealing technique with a time-dependent annealing process in vacuumed quartz tubes. ThCr2Si2 -type crystal structure was concluded for both samples varying with in- and out-of-plane lattice parameters. The superconducting critical temperatures were determined by resistivity and under H=20 Oe magnetization measurements, which were performed between the temperature ranges of 0-200 K. The upper and lower critical fields were determined and possible Meissner effects were roughly figured out to understand the level of shielding from M-H measurements. The maximum critical temperature was obtained from Ca0.9La0.1Fe1.9Pt0.1As2.
Keywords: Current density; Meissner effect; La and Pt dopant effect; superconductivity; HIGH-TEMPERATURE SUPERCONDUCTIVITY